Performance‐Emission Optimization of a Diesel Engine Blended With Biodiesel and Pentanol - Geetesh Goga; Deepam Goyal; Tarun Goyal; Krupakaran Radhakrishnan Lawrence; P. V. Elumalai; Sunil Kumar Mahla; Anil Singh Yadav; Subhendu Chakroborty; Nasim Hasan (Energy Science & Engineering)
ABSTRACT The quest for novel alternative fuel blends is fueled by the urgent need to address the inadequacy of fossil fuels and the escalating environmental concerns. While previous studies have primarily explored base fuel and minimally diluted alcohol content since the late 20th century, a significant research gap exists in the comparative analysis of biodiesel and alcohol blends. In this article, an attempt has been made to bridge that gap by investigating fuel mixtures containing varying proportions (5%–20%) of Jatropha oil‐based biodiesel (JOBD) and Pentanol, evaluated across different Engine load (EL), JOBD, and Pentanol concentrations. Experimentation was conducted on a 4‐stroke, single cylinder, direct injection vertical engine. A comprehensive experimental analysis was performed using the Taguchi approach and ANOVA by MINITAB17®, to assess key engine performance and emission characteristics—namely hydrocarbons (HC) emissions, brake‐specific fuel consumption (BSFC), carbon monoxide (CO) emissions, and brake thermal efficiency (BTE). The higher values of raw data and S/N ratio for BTE were observed in the order of A3B1C1 and lower raw data and higher S/N values were achieved for BSFC, CO and HC as A3B1C1, A3B3C3 and A3B3C3 respectively. The higher values of S/N ratios for higher raw data values of BTE and lower values of BSFC, CO and HC were found to be in complete agreement to each other. The findings contribute the potential of biodiesel‐pentanol blends as sustainable alternatives, promoting environmentally friendly solutions for the automotive industry.